Carbon-coated Si particles with self-supported Si nanowires as anode material for lithium-ion batteries. (4th July 2018) - Qu, Fangmu; She, Guangwei; Wang, Jiantao; Qi, Xiaopeng; Zhang, Shaoyang; Li, Shengyang; Mu, Lixuan; Shi, Wensheng
Abstract: Although extremely high specific capacity has been envisioned for Si anode materials, the application of Si in lithium-ion batteries (LIBs) is still hampered due to the rapid capacity fading mainly caused by the huge volume changes during the cycling. In this study, carbon-coated Si particles with self-supported Si nanowires were prepared using low-cost raw materials by a versatile and scalable method and investigated as anode materials in LIBs. The single Si particle with size of about 30 ∼ 40 μ m is composed of a solid Si core and numerous porous Si nanowires radially distributed on the Si core. This unique architecture can effectively accommodate the volume expansion of Si, release the mechanical stress, prevent the aggregation of Si nanowires and keep the structural integrity. Utilized as anode materials for LIBs, the as-prepared carbon-coated Si particles show improved cycle stability and high initial coulombic efficiency than the raw metallurgical Si particles.